2015
DOI: 10.5493/wjem.v5.i4.225
|View full text |Cite
|
Sign up to set email alerts
|

Disease control by regulation of P-glycoprotein on lymphocytes in patients with rheumatoid arthritis

Abstract: The main purpose of treatment of rheumatoid arthritis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…P-gp reacts differently to the three types of substrate [ 31 ]. Controversy remains as to whether MTX is a complete substrate for P-gp, with some studies suggesting it is [ 7 , 28 ], and others arguing that it is not [ 31 ]; nevertheless, it is clear that MTX has an obvious effect on P-gp [ 8 10 ]. The interaction between MTX and P-gp may involve factors in addition to the efflux pump.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P-gp reacts differently to the three types of substrate [ 31 ]. Controversy remains as to whether MTX is a complete substrate for P-gp, with some studies suggesting it is [ 7 , 28 ], and others arguing that it is not [ 31 ]; nevertheless, it is clear that MTX has an obvious effect on P-gp [ 8 10 ]. The interaction between MTX and P-gp may involve factors in addition to the efflux pump.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to serving as the primary treatment for RA, MTX is a specific substrate of P-gp [ 7 ]. Several studies have demonstrated P-gp overexpression in the lymphocytes or synovial cells of MTX-resistant RA patients [ 8 10 ]. Treatment with the P-gp inhibitors, cyclosporine A and tacrolimus, has been shown to significantly improve the clinical symptoms and laboratory indicators in RRA patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of immunosuppressants is well defined. Calcineurin inhibitors (ciclosporin), mTor inhibitors (sirolimus alternative name rapamycin) and cell cycle blockers (mycophenolate mofetil) have been used widely for many years in the treatment of various diseases such as scleroderma, multiple sclerosis, lupus erythematosus and rheumatoid arthritis, with significant efficacy …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…P-glycoprotein (P-gp)-mediated drug resistance P-gp, also known as multidrug resistance protein 1 (MDR1) or CD243, is an important membrane pumps for the cellular removal of foreign substances. In patients with refractory RA and high disease activity, overexpression of P-gp on lymphocytes can cause resistance to antirheumatic drugs through efflux of intracellular drugs [134]. Recent studies further showed that high expression level of P-gp found in FLS of refractory RA patients is the potential mechanism for multidrug resistance in RA treatment [135].…”
Section: From Intervention To Innovation: Implication Of Conventionalmentioning
confidence: 99%